NMR Spectroscopic Characterization of the C‐Mannose Conformation in a Thrombospondin Repeat Using a Selective Labeling Approach. (3rd September 2020) - Jonker, Hendrik R. A.; Saxena, Krishna; Shcherbakova, Aleksandra; Tiemann, Birgit; Bakker, Hans; Schwalbe, Harald
Abstract: Despite the great interest in glycoproteins, structural information reporting on conformation and dynamics of the sugar moieties are limited. We present a new biochemical method to express proteins with glycans that are selectively labeled with NMR‐active nuclei. We report on the incorporation of 13 C‐labeled mannose in the C‐mannosylated UNC‐5 thrombospondin repeat. The conformational landscape of the C‐mannose sugar puckers attached to tryptophan residues of UNC‐5 is characterized by interconversion between the canonical 1 C4 state and the B03 / 1 S3 state. This flexibility may be essential for protein folding and stabilization. We foresee that this versatile tool to produce proteins with selectively labeled C‐mannose can be applied and adjusted to other systems and modifications and potentially paves a way to advance glycoprotein research by unravelling the dynamical and conformational properties of glycan structures and their interactions. Abstract : NMR spectroscopy was used to characterize the C‐mannose conformation in a thrombospondin repeat using a selective labeling approach. The conformational landscape of the C‐mannose sugar puckers attached to tryptophan residues of the netrin receptor UNC‐5 allows interconversion between the canonical 1 C4 state and the B03 / 1 S3 state.